PENGARUH PENERAPAN STRATEGI PEMBELAJARAN THINK-TALK-WRITE (TTW) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN KOMUNIKASI MATEMATIKA MAHAMAHASISWA STKIP MUHAMMADIYAH MUARA BUNGO - Sundahry Dahry (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
Mathematics is the basis for the development of science and technology because mathematics can develop the ability to think logically, analytically, critically, creatively and systematically as well as the ability to work together. In the pre-observation, mathematical concepts and communication problems were found in STKIP MB. This research is an experimental research conducted in two classes, there is a control class and an experimental class. The control class was not given treatment while the experimental class was given treatment. The results showed that the ability to understand mathematical concepts of students who received the TTW learning strategy with an average score of 2.6 was higher than that of students who received conventional learning strategies with an average score of 2.2. The mathematical communication ability of students who received the TTW learning strategy with an average score of 2.6 was higher than that of students who received conventional learning strategies with an average score of 2.1. So the TTW model is effective to use.